External validation of a nomogram predicting risk of bleeding control interventions after high-grade renal trauma: The Multi-institutional Genito-Urinary Trauma Study. Issue 2 (February 2021) - Keihani, Sorena; Wang, Sherry S.; Joyce, Ryan P.; Rogers, Douglas M.; Gross, Joel A.; Nocera, Alexander P.; Selph, J. Patrick; Fang, Elisa; Hagedorn, Judith C.; Voelzke, Bryan B.; Rezaee, Michael E.; Moses, Rachel A.; et al.
Abstract : BACKGROUND: Renal trauma grading has a limited ability to distinguish patients who will need intervention after high-grade renal trauma (HGRT). A nomogram incorporating both clinical and radiologic factors has been previously developed to predict bleeding control interventions after HGRT. We aimed to externally validate this nomogram using multicenter data from level 1 trauma centers. METHODS: We gathered data from seven level 1 trauma centers. Patients with available initial computed tomography (CT) scans were included. Each CT scan was reviewed by two radiologists blinded to the intervention data. Nomogram variables included trauma mechanism, hypotension/shock, concomitant injuries, vascular contrast extravasation (VCE), pararenal hematoma extension, and hematoma rim distance (HRD). Mixed-effect logistic regression was used to assess the associations between the predictors and bleeding intervention. The prediction accuracy of the nomogram was assessed using the area under the receiver operating characteristic curve and its 95% confidence interval (CI). RESULTS: Overall, 569 HGRT patients were included for external validation. Injury mechanism was blunt in 89%. Using initial CT scans, 14% had VCE and median HRD was 1.7 (0.9–2.6) cm. Overall, 12% underwent bleeding control interventions including 34 angioembolizations and 24 nephrectomies. In the multivariable analysis, presence of VCE was associated with a threefold increase in the odds of bleeding interventions (odds ratio, 3.06; 95% CI, 1.44–6.50). Every centimeter increase in HRD was associated with 66% increase in odds of bleeding interventions. External validation of the model provided excellent discrimination in predicting bleeding interventions with an area under the curve of 0.88 (95% CI, 0.84–0.92). CONCLUSION: Our results reinforce the importance of radiologic findings such as VCE and hematoma characteristics in predicting bleeding control interventions after renal trauma. The prediction accuracy of the proposed nomogram remains high using external data. These variables can help to better risk stratify high-grade renal injuries. LEVEL OF EVIDENCE: Prognostic and epidemiological study, level III.